2008
DOI: 10.1111/j.1468-1293.2008.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Standard‐dose efavirenz vs. standard‐dose nevirapine in antiretroviral regimens among HIV‐1 and tuberculosis co‐infected patients who received rifampicin

Abstract: There is limited comparative data between efavirenz (EFV) 600 mg/day and nevirapine (NVP) 400 mg/day-based antiretroviral therapy (ART) among HIV-1 patients with tuberculosis (TB) and receiving rifampicin. MethodsA retrospective cohort study was conducted in all ART-naïve patients who were receiving rifampicin between January 2002 and December 2005. ResultsOf 188 patients, 77 and 111 patients were initiated on EFV-based ART (EFV group) and NVP-based ART (NVP group), respectively. Overall, median [interquartile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 26 publications
4
29
1
Order By: Relevance
“…This is in agreement with that suggested by others, who observed excellent clinical outcomes when giving EFV at 600 mg/day to patients receiving RMP (11,22,27,28). A study conducted with HIV-TB patients receiving EFV at 600 mg/day and RMP reported virological success in about 80% of the patients studied at 48 weeks of treatment (24). In a comparative study of two groups of HIV-infected patients receiving EFV at 600 and 800 mg/day, Manosuthi et al did not observe any difference in plasma EFV levels and time to virological success (23).…”
Section: Discussionsupporting
confidence: 80%
“…This is in agreement with that suggested by others, who observed excellent clinical outcomes when giving EFV at 600 mg/day to patients receiving RMP (11,22,27,28). A study conducted with HIV-TB patients receiving EFV at 600 mg/day and RMP reported virological success in about 80% of the patients studied at 48 weeks of treatment (24). In a comparative study of two groups of HIV-infected patients receiving EFV at 600 and 800 mg/day, Manosuthi et al did not observe any difference in plasma EFV levels and time to virological success (23).…”
Section: Discussionsupporting
confidence: 80%
“…A recent Malawian study 30 found that 59% of patients coinfected with HIV and tuberculosis had subtherapeutic nevirapine concentrations during the lead-in dosing phase. A Thai study that compared patients initiating efavirenz-based or nevirapinebased ART with concurrent tuberculosis reported an OR between these groups for achieving a viral load lower than 50 copies/mL at 48 weeks of 0.590 (95% CI, 0.302-1.153) 22 but was based on smaller numbers of patients.…”
Section: Underlying Mechanismsmentioning
confidence: 96%
“…9,[11][12][13][14][15][16] Nevirapine has a higher risk of hepatotoxicity than efavirenz, althoughonlyasmallproportionofpatients develop clinical hepatitis. [17][18][19] There are 3 small published studies (32 patients fromSpain 20 and70patients 21 and111pa-tients from Thailand 22 ) that suggest that nevirapine can be safely and effectively coadministeredwithrifampicin.However, thefindingsfromtheThaistudiesmaynot be generalizable to other populations due to ethnic differences in drug effects and the low body weight of the patients, and the Spanish study was retrospective without a comparison group. Thus a need for more studies exists, particularly from Africa where approximately 85% of HIV-associated cases of tuberculosis occur.…”
mentioning
confidence: 99%
“…Regimens recommended for use in India for patients with concomitant TB are a combination of 2 NRTI's with Efavirenz or less commonly Nevirapine. The NRTI combinations used commonly are Zidovudine with Lamivudine, Stavudine with Lamivudine, Tenofovir with Lamivudine, and rarely Abacavir with Lamivudine or Didanosine with Lamivudine (only the fi rst two combinations are available in the national program) (National AIDS Control Organization 2007) There is some preliminary data to suggest that nevirapine can be safely given with rifampicin, but results of ongoing clinical trials are awaited (Manosuthi et al 2006(Manosuthi et al , 2008Cohen et al 2008). Among the PI's, nelfi navir, saquinavir, lopinavir and ritonavir can be used but additive hepatoxicity may occur with anti-TB drugs requiring close monitoring of liver function.…”
Section: Anti-retroviral Treatmentmentioning
confidence: 99%